Візантійські походи київських князів в історичній пам’яті східного слов’янства - Ричка, В.М. (Український історичний журнал, 2012)
З’ясовується історичне значення походів київських князів на Візантію, які під мурами Царгорода вкрили себе невмирущою «грецькою славою». Простежується осмислення цієї спадщини на заломах історичної пам’яті наступних поколінь, її вплив на формування культурно-політичних ідентичностей східнослов’янських народів та вибір шляхів їх цивілізаційного розвитку. Ascertained in the article the historical importance of marches to Byzantine Empire that were headed by Kyivan princes. Under the walls of Tsarhorod they covered themselves with the everlasting “Greek Glory”. The author retraces the comprehension of this inheritance on the refractions of historical memory of next generations, its influence on the formation of cultural-political identities of the nations of Eastern Slavs and choice of the ways of their civilized evolution.